1969
DOI: 10.2136/sssaj1969.03615995003300010023x
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Cation Complexes in Soil Solution: IV. The Chemical State of Manganese in Soil Solution

Abstract: Soil solutions from several areas of the US were analyzed by atomic absorption for total Mn and by resin exchange for percent Mn complexed. Values for the latter (84%–99%) in soil solution from the A horizon were intermediate to those previously reported for Zn and Cu. Soil solution from a New York forest soil at pH 7 contained 13 ppm Mn, of which 93% was complexed. Spectrophotometric and polarographic methods were developed to determine the oxidation state of Mn in this soil solution. Both methods indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Acid soils contain much soluble AI, Mn, and Fe, and in neutral soils Mn and Fe can be released in large quantities when reducing conditions prevail after waterlogging (Ponnamperuma, 1972). Geering et al (1969) found that soil solution Mn concentrations in a silt loam varied 100-fold during one year as a result of seasonal influences. Many soils are grossly polluted with heavy metals as a result of man's activities of mining and smelting.…”
Section: B Phmentioning
confidence: 99%
“…Acid soils contain much soluble AI, Mn, and Fe, and in neutral soils Mn and Fe can be released in large quantities when reducing conditions prevail after waterlogging (Ponnamperuma, 1972). Geering et al (1969) found that soil solution Mn concentrations in a silt loam varied 100-fold during one year as a result of seasonal influences. Many soils are grossly polluted with heavy metals as a result of man's activities of mining and smelting.…”
Section: B Phmentioning
confidence: 99%
“…The complexation properties of Na, Cu, Zn, and Mn (almost equally retained) are of particular importance for employing humic substances in the fertilizer production lines; the Cu-and Zn-humic complexes proved valuable, significantly increasing the plant uptake and the shoot and root dry weight (Garcia-Mina et al, 2004). Moreover, Hodgson et al (1965), Hodgson (1966) and Geering et al (1969) reported that in limy, alkaline soil solutions most of the Cu, Zn, and Mn were present in the form of organic matter complexes. In addition, Cu and Zn demonstrate complexation activity varying with the molecular mass of the humic substances studied (Nifant'eva et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…This chemical feature of HS improves physical soil properties favoring the formation of stable clay-humic aggregates through cation bridges, and soil fertility increasing mineral nutrient (P, Fe, Mn or Zn) availability for plants grown in alkaline and calcareous soils [15]. In fact, several studies have reported that a very significant fraction of Cu, Zn, Fe and Mn in soil solution from limy, alkaline soils was present in the form of complexes with DOM [16][17][18].…”
Section: Main Hs-ie On Plant Growth and Mineral Nutritionmentioning
confidence: 99%